2015
DOI: 10.1039/c5cp04131g
|View full text |Cite
|
Sign up to set email alerts
|

A weight averaged approach for predicting amide vibrational bands of a sphingomyelin bilayer

Abstract: Infrared (IR) and Raman spectra of a sphingomyelin (SM) bilayer have been calculated for the amide I, II and A modes and the double-bonded CC stretching mode by a weight averaged approach, based on an all-atom molecular dynamics (MD) simulation and a vibrational structure calculation. Representative structures and statistical weights of SM clusters connected by hydrogen bonds (HBs) are observed in MD trajectories. After constructing smaller fragments from the SM clusters, the vibrational spectra of the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 73 publications
1
20
0
Order By: Relevance
“…[1,19,51,52] In an impressive recent study, Yagi et al demonstrated the persistency and versatility of hydrogen bonding formation in SM clusters through the interpretation of amide vibrational bands for an SM bilayer. [53] In line with past observations, we observe stable CHOL-SM heterodimers in ternary lipid mixtures (Fig. 10).…”
Section: Chol Forms Persistent Hydrogen Bonds With Smsupporting
confidence: 93%
See 1 more Smart Citation
“…[1,19,51,52] In an impressive recent study, Yagi et al demonstrated the persistency and versatility of hydrogen bonding formation in SM clusters through the interpretation of amide vibrational bands for an SM bilayer. [53] In line with past observations, we observe stable CHOL-SM heterodimers in ternary lipid mixtures (Fig. 10).…”
Section: Chol Forms Persistent Hydrogen Bonds With Smsupporting
confidence: 93%
“…There is substantial support from experimental and computational studies for the importance of hydrogen bonding interaction between CHOL and SM . In an impressive recent study, Yagi et al demonstrated the persistency and versatility of hydrogen bonding formation in SM clusters through the interpretation of amide vibrational bands for an SM bilayer …”
Section: Resultsmentioning
confidence: 99%
“…Details of the computational procedure have been given elsewhere (15). An MD simulation of the SM bilayer was conducted using an all-atom force field for SM (16).…”
Section: Simulationmentioning
confidence: 99%
“…The method for calculating the IR difference spectrum presented here extends the method suggested in ref . The method is trivially extendable to other systems containing many similar chromophores, for example, other polymer and solvent systems.…”
Section: Discussionmentioning
confidence: 94%
“…Unlike simple molecular clusters or solids, complex systems have an enormous number of structures (such as H-bond patterns) that contribute to the vibrational spectrum. Recently, we have proposed a weight-averaged approach to calculate the IR and Raman spectra of sphingomyelin (SM) bilayers at different phases. , In this method, molecular dynamics (MD) simulations are first carried out to sample H-bond patterns of amide groups in SM and water molecules. Then, for each pattern, the MD trajectory is used to construct a cluster model, and the harmonic vibrational spectrum is computed using DFT.…”
Section: Introductionmentioning
confidence: 99%